Pre-operative hemoglobin level and use of sedative-hypnotics are independent risk factors for post-operative delirium following total knee arthroplasty - Eiji Kijima; Tomohiro Kayama; Mitsuru Saito; Daisaburo Kurosaka; Ryo Ikeda; Hiroteru Hayashi; Daisuke Kubota; Takashi Hyakutake; Keishi Marumo (BMC Musculoskeletal Disorders, 2020)
Abstract Background Delirium is a well-known complication following surgery, especially with the increasing age of patients undergoing surgery. The increasing demands resulting from a prolonged healthy life expectancy has resulted in more arthroplasties despite their age and existing comorbidities. The purpose of this study is to explore the various risk factors that may contribute to delirium in unilateral and bilateral total knee arthroplasties in the elderly population. Methods 170 patients who underwent unilateral or bilateral total knee arthroplasties were analyzed retrospectively for delirium. Age, sex, comorbidities, use of sedative-hypnotics, peri-operative blood loss, pre- and post-operative laboratory blood test results were investigated and analyzed. Results The incidence of post-operative delirium was 6.5% (11 out of 170 patients) with a mean age of 79.5 (± 6.9) years, compared to 73.0 (± 9.0) years in the non-delirium group. Higher age, use of sedative-hypnotics, low pre-operative Hb and Ht, low post-operative Hb, Ht and BUN were observed in the delirium group. Multivariate logistic regression analysis identified that the use of sedative-hypnotics and pre-operative Hb level were independent risk factors for post-operative delirium after TKA. The odds ratios for the use of sedative-hypnotics and pre-operative Hb level were 4.6 and 0.53, respectively. Receiver operating characteristic curve analysis showed that pre-operative Hb of less than 11.1 g/dL was a predictor for the development of delirium, with a sensitivity of 54.6% and a specificity of 91.6%. Conclusion Patients with a pre-operative Hb level of < 11.1 g/dL or those using sedative-hypnotics are associated with post-operative delirium. Peri-operative management and preventative measures are therefore needed to reduce the risks of post-operative delirium in such patients.